2018
DOI: 10.3906/zoo-1802-42
|View full text |Cite
|
Sign up to set email alerts
|

Contribution and acclimatization of the swarming tropical copepod Dioithona oculata (Farran, 1913) in a Mediterranean coastal ecosystem

Abstract: Introduction The eastern Mediterranean is sensitive to alien invasions due to its geographic position (i.e., its connection with Atlantic Ocean, Black Sea, and Erythrean regions), crowded maritime traffic, fisheries, and tourism activities in the coastal regions (Galil and Zenotos, 2002). Alien species increased after the opening of the Suez Canal in 1869 and construction of the Aswan Dam (Galil, 2000); hundreds of alien species passed through the Suez Canal to the Mediterranean Sea, forming thriving populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…P. marinus could have been transported by the longshore current from the Israeli coast into ˙Iskenderun Bay or through ship ballast waters. ˙Iskenderun Bay has many national and international harbours and ports that facilitate NIS introductions [52,53].…”
Section: Western Mediterranean Seamentioning
confidence: 99%
“…P. marinus could have been transported by the longshore current from the Israeli coast into ˙Iskenderun Bay or through ship ballast waters. ˙Iskenderun Bay has many national and international harbours and ports that facilitate NIS introductions [52,53].…”
Section: Western Mediterranean Seamentioning
confidence: 99%
“…Bu türün Akdeniz'de varlığı ilk kez 2013 yılında İskenderun Körfezi'nde tespit edilmiştir (Terbıyık Kurt, 2018). Levant Denizi dışında herhangi bir alanda gözlenmemiş olmakla birlikte, farklı alanlarından da dağıldığına dair henüz bir bilgi bulunmamaktadır.…”
Section: Introductionunclassified
“…Among the 50 alien zooplankton species that were recorded in the Mediterranean Sea, only 12 copepod species were established in this region (Zenetos et al, ). In recent years, the number of introduced alien copepod species increased, and there have been new additions day by day (Olazabal & Tirelli, ; Ounissi, Laskri, & Khelifi‐Touhami, ; Terbıyık Kurt, ; Zagami, Costanzo, & Crescenti, ; Zenetos et al, ). According to a recent study, 18 alien Copepoda species were found in the Mediterranean coast of Turkey; six of them were reported in the coast of the Aegean Sea (Bakir et al, ).…”
Section: Introductionmentioning
confidence: 99%